2000
DOI: 10.1074/jbc.m005355200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the cDNAs Coding for Two Novel Molybdo-flavoproteins Showing High Similarity with Aldehyde Oxidase and Xanthine Oxidoreductase

Abstract: The cDNAs coding for two novel mouse molybdo-flavoproteins, AOH1 and AOH2 (aldehyde oxidase homolog 1 and 2), were isolated. The AOH1 and AOH2 cDNAs code for polypeptides of 1336 amino acids. The two proteins have similar primary structure and show striking amino acid identity with aldehyde oxidase and xanthine oxidoreductase, two other molybdo-flavoenzymes. AOH1 and AOH2 contain consensus sequences for a molybdopterin-binding site and two distinct 2Fe-2S redox centers. In its native conformation, AOH1 has a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
113
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(119 citation statements)
references
References 56 publications
5
113
1
Order By: Relevance
“…Recently we demonstrated that the molybdo-flavoenzyme family is larger than previously anticipated (12,13). In fact, we identified two novel proteins characterized by high structural similarities with AOX1 and XOR (12,13).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Recently we demonstrated that the molybdo-flavoenzyme family is larger than previously anticipated (12,13). In fact, we identified two novel proteins characterized by high structural similarities with AOX1 and XOR (12,13).…”
mentioning
confidence: 90%
“…The polyclonal anti-XOR antibody was raised against the synthetic peptide, NH 2 -NTMKTQSFIAKH-COOH, according to an established methodology (12). The anti-AOH1, anti-AOX1, anti-AOH2, and anti-XOR rabbit antisera were used for Western blot analyses, which were carried out with a chemiluminescence-based protocol as described previously (12,13,18,19). SDS-PAGE was performed according to standard techniques (20).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations